Genetic Mutations in TNFSF11 Were Associated With the Chronicity of Hepatitis C Among Chinese Han Population - Huang, Peng; Hou, Yu-Qing; Wu, Jing-Jing; Wang, Yi-Di; Ye, Xiang-Yu; Zang, Feng; Yu, Rong-Bin; Yang, Sheng (Frontiers in Medicine, 2021)
Background: Recently, several studies have reported that the host immune response can be related to the RANKL/RANK/OPG signaling pathway. However, the associations of TNFSF11, TNFRSF11A, and TNFRSF11B gene polymorphisms in the RANKL/RANK/OPG pathway with hepatitis C virus (HCV) infection outcomes remain unclear. Methods: In this case-control study, 768 persistent HCV infection and 503 spontaneous HCV clearance cases, and 1259 control subjects were included. The TaqMan-MGB probe method was utilized to detect TNFSF11 rs9525641, TNFRSF11A rs8686340 and TNFRSF11B rs2073618 genotypes. The distribution of three single nucleotide polymorphisms (SNPs) genotypes was analyzed using stata14.0. Results: SNPs rs9525641, rs8086340, and rs2073618 genotype frequencies followed the Hardy-Weinberg natural population equilibrium (p = 0.637, 0.250, and 0.113, respectively). Also, rs9525641 was significantly associated with HCV chronicity risk in recessive (OR = 1.203, 95% CI: 1.018-1.420, p = 0.030) and additive models (OR = 1.545, 95% CI: 1.150-2.075, p = 0.004). The stratified analysis showed that rs9525641 variant genotypes were associated with HCV chronicity among people older than 50 years (OR =1 .562, 95% CI: 1.079-2.262, p = 0.018), females (OR = 1.667, 95% CI: 1.145-2.429, p = 0.008), ALT < 40 U/L (OR = 1.532, 95% CI: 1.074-2.286, p = 0.018), and AST < 40 U/L (OR = 1.552, 95% CI: 1.095-2.201, p = 0.014). Conclusion: TNFRSF11 rs9525641 was significantly associated with HCV chronicity in the Chinese population.